Experimental and numerical study of concrete frames with steel plate shear walls. (September 2022) - Parvizi, Mehdi; Fathi, Mojtaba; Zamani, Seyed Sohail Majid; Shakib, Hamzeh; Karami, Aminallah
Abstract: Steel plate shear wall systems have appropriate behavior in high seismic zones. They could be combined with concrete or precast concrete structures to compensate susceptibility of these structures to strong earthquakes. This article presents an experimental and numerical study on seismic behavior of various types of steel plate shear walls installed in simple and rigid concrete frames. These frames were subjected to quasi-static cycling loading in accordance with ACI T1.1–01. Compared to the bare moment frame, erection of the steel plate in simple concrete frame by bearing bolted connection led to an increase in lateral load capacity, initial stiffness, energy dissipation and equivalent hysteretic damping up to 1.7, 2.2, 3.5 and 3 times, respectively. These ratios for the steel plate shear wall with moment frame, and connected by friction bolted connections were 3, 7.2, 7.7 and 3.2 times. The horizontal and vertical stiffeners in the steel plate shear wall with the openings over the main diameters contributed to 13% and 27% increase in energy dissipation and equivalent damping, respectively, while the load bearing capacity and initial stiffness did not decrease significantly. At the bearing bolted connections, crippling and tearing of the steel plate was observed, but no any damage occurred at the friction bolted connections. Whereas, all the steel connecting components embedded in concrete were in the elastic range and also, equations governing the angle of inclination of the tensile field, were valid. Finally, the samples were simulated in Abaqus finite element software, and the pushover curves of experimental load-displacements diagrams were predicted. Highlights: Using steel plate shear wall system in precast concrete structures improves seismic behavior. Steel plate shear wall with stiffened openings over main diameters enhances ductility, damping and energy dissipation, without strength and stiffness reduction. Using individual embedded steel belts in concrete boundary elements, is a novel system to connect steel plate to concrete boundary elements. Connecting the steel shear wall to connection belts by friction type bolted connection, enhances seismic and structural properties, and dose not damage the steel plate. The tension field is more intense at the corners of steel plate shear wall and are the starting points of yielding.